2019
DOI: 10.1016/j.jvs.2018.10.047
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of low-fidelity virtual reality simulators compared with other learning methods in basic endovascular skills training

Abstract: Objective: The use of simulators has shown a profound impact on the development of both training and assessment of endovascular skills. Furthermore, there is evidence that simulator training is of great benefit for novice trainees. However, there are only a few simulators available geared specifically toward novice learners. Whereas research suggests that low-fidelity simulators could fill this gap, there are insufficient data available to determine the role of low-fidelity simulators in the training of endova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Interventional radiology, which is one aspect of surgery, encompasses minimally invasive procedures, translating into lower cost, less morbidity, and shorter hospital stays (12) . The greatest difficulties found during the process of learning interventional radiology procedures involve spatial and cognitive proprioception, as well as motor difficulties in using the new equipment, which can have catastrophic consequences at the beginning of a career (14,22) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventional radiology, which is one aspect of surgery, encompasses minimally invasive procedures, translating into lower cost, less morbidity, and shorter hospital stays (12) . The greatest difficulties found during the process of learning interventional radiology procedures involve spatial and cognitive proprioception, as well as motor difficulties in using the new equipment, which can have catastrophic consequences at the beginning of a career (14,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Institutions such as the European Board of Vascular Surgery and the German Society for Vascular Surgery and Vascular Medicine have already implemented or expressed an interest in including simulation-based training as a compulsory part of medical education (14) . However, it remains unknown which simulators are most effective for teaching, in which populations they should actually be implemented, and for what purposes they are indicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LF simulation in endovascular procedures was shown to improve motivation in novice trainees but does not necessarily improve practical skills. 40 In one study of psychological stress, junior residents had significantly increased stress during HF simulation compared to LF simulation, while senior surgeons showed no differences. 41 It was also suggested that HF simulators might result in poorer performance by novice trainees because they are over-stimulated by the HF environment.…”
Section: Discussionmentioning
confidence: 99%
“…9 Finally, AI has also been developed to enable simulation used for the training in vascular surgery. 10 These examples prove that the development of AI together with BD is a major opportunity for vascular surgeons, as these techniques have the potential to improve patient care, evidence based medicine, education, and training. AI has raised promises but, on the downside, has created hype derived from fantasy.…”
mentioning
confidence: 99%